Host preference and eco-friendly management of cucurbit fruit fly under field condition of Bangladesh - Sultana, Tanzila; Uddin, Mohammad Mahir; Rahman, Md Mahbubur; Shahjahan, Md (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
Experiments were carried out to investigate the host preference of cucurbit fruit fly, Bactrocera cucurbitae and its management to cucurbitaceous vegetables namely, bitter gourd, ridge gourd and snake gourd. Among the vegetables, bitter gourd was found as mostly preferable (upto 40.69% fruit infestation) and snake gourd was found as the least preferable (18.64% fruit infestation). Among management tactics (fruit bagging, neem oil, mahogany oil, alamonda leaf extract, pheromone trap and cider vinegar traps), bagging reduced maximum fruit infestation (upto 75.51%) compared to controlled plots. Among the botanicals, neem oil was mostly effective (21.64% reduction of fruit infestations) followed by alamonda leaf extract and mahogany oil. Both traps were found effective and more insect were trapped in the pheromone trap. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 55-59